1998
DOI: 10.1080/00909889809365514
|View full text |Cite
|
Sign up to set email alerts
|

A dialectical analysis of a social justice process: International collaboration in South Africa

Abstract: This paper presents a case study of an international team collaboration between US and South African conflict specialists and educators implementing a Community Peace and Safety Network in four communities in the Gauteng province of SouthAfrica. The project, funded by the United States Information Agency, was a social justice initiative that provided mediation training for school and community centers to aid them in accomplishing constructive conflict management and social change. Following an overview of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…By challenging the "us" versus "them" divide, she uncovered how negotiation paradoxically minimized violence between the two religious groups while affirming their opposing intra-group identities. Similarly, rather than relying on historically-defined ethnic identities, Jones and Bodtker (1998) studied how educators navigated the paradoxes of power (both gaining and losing power) between the US and South Africa through embracing the interplay of opposites. Paradox also surfaced in Donohue's (2001) relational model of negotiation that focused on embracing both cooperation and competition through juxtaposing high and low interdependence and high and low affiliations.…”
Section: Embracing the Gender/negotiation Paradoxmentioning
confidence: 99%
“…By challenging the "us" versus "them" divide, she uncovered how negotiation paradoxically minimized violence between the two religious groups while affirming their opposing intra-group identities. Similarly, rather than relying on historically-defined ethnic identities, Jones and Bodtker (1998) studied how educators navigated the paradoxes of power (both gaining and losing power) between the US and South Africa through embracing the interplay of opposites. Paradox also surfaced in Donohue's (2001) relational model of negotiation that focused on embracing both cooperation and competition through juxtaposing high and low interdependence and high and low affiliations.…”
Section: Embracing the Gender/negotiation Paradoxmentioning
confidence: 99%
“…Conflict by definition is a mixed‐motive activity that embraces contradiction through simultaneously engaging in cooperation and competition, trust and distrust, and information concealing while revealing. Research programs are replete with a host of dualities that cross studies on relational paradoxes (Donohue, ), dialectics in mediation (Jones, ), and binaries that underlie organizational and social justice disputes (Jameson, ; Jones & Bodtker, ). Although the field has produced excellent exemplars of conflict as paradoxical and dialectical process, scholars need to integrate this work and then theorize from it to develop dimensions, processes, strategies, and practices linked to conflict transformation.…”
Section: A Dialogue With Linda L Putnammentioning
confidence: 99%
“…Dialogic scholarship also provides a vocabulary for that which impedes the ability of collaborative stakeholders to share power. Jones and Bodtker (1998) suggested that contestation plays an important role in collaborative problem solving. Hence, discursive closure, the inability to contest something (Deetz, 1990(Deetz, , 1992(Deetz, , 1995, presents a challenge to achieving dialogue in community collaboration.…”
Section: Rethinking Community Collaboration Through Dialogic Theoriesmentioning
confidence: 99%